Characteristics of Body Mass Index Based on Physical Activity among Medical Students - Nabilah Putri Audya; Armanto Makmun; Windy Nurul Aisyah; Imran Safei; Sigit Dwi Pramono (Ann Publisher, 2026)
Background: Nutritional status, commonly assessed using Body Mass Index (BMI), is a key indicator of health among young adults. Modern sedentary lifestyles and increasing academic demands may contribute to imbalanced BMI, particularly among medical students who often experience limited physical activity. Aim: This study aimed to describe the characteristics of Body Mass Index based on physical activity levels among medical students of the Faculty of Medicine, Universitas Muslim Indonesia, Class of 2022. Methods: A descriptive quantitative study with a cross-sectional design was conducted involving 84 medical students selected through simple random sampling. Body weight and height were measured to calculate BMI, which was categorized according to WHO criteria. Physical activity levels were assessed using the Global Physical Activity Questionnaire (GPAQ) and classified into low, moderate, and high activity based on MET-minutes per week. Data were analyzed descriptively and presented as frequencies and percentages. Results: Most respondents were female (75.0%) and aged 20–22 years. The majority had a normal BMI (42.9%); however, substantial proportions were underweight (23.8%) or obese (19.1%). Physical activity levels were predominantly low (44.0%) or moderate (40.5%), with only 15.5% reporting high activity. Students with moderate physical activity tended to have normal BMI, whereas low physical activity was more frequently observed among underweight and obese students. Higher BMI categories were generally associated with lower physical activity levels. Conclusion: Most medical students exhibited low to moderate physical activity, accompanied by varied BMI profiles. These findings highlight the importance of promoting regular physical activity to support optimal nutritional status among medical students.